MENINGKATKAN HASIL BELAJAR PKN DENGAN MENGGUNAKAN MODEL ROLE REVERSAL QUESTION SISWA KELAS IX SMP NEGERI 1 WRINGIN PADA SEMESTER GANJIL TAHUN PELAJARAN 2018/2019: SMP NEGERI 1 WRINGIN - GENDUT SUNARTO (Dewan Pendidikan Bondowoso, 2021)
Education is a learning experience that takes place in the environment and is obtained throughout life. Education is carried out by the family, community and government. This is in accordance with the definition of education according to Redja Mudyaharjo (2012), namely: